Distributed power control for 5G millimeter wave dense small cell - Salh, Adeb; Mohd Shah, Nor Shahida; Audah, Lukman; Mohd Shah, Shaharil; Hamzah, Shipun Anuar (Institute of Advanced Scientific Research, 2020)
The millimeter wave (mm-wave) is one of the key enabling elements in the fifth generation (5G) technology that uses highly directional beamforming to mitigate path loss by using antenna arrays. The mmwave for massive multiple-input-multiple-output (MIMO) is able to reduce the cross-tier interference between multiple antennas to assist the number of active users (UEs). The dense small cell is very important to increase the capacity and high coverage in cell edge. This paper focuses on achievable high data rate in a dense small cell based on the use of mm-wave. In order to perform the achievable high data rate, a novel distributed power allocation is proposed in this work that reduces the high path loss and suppresses cross-tier interference under constraint transmission power in mm-wave. The condition of the Nash Equilibrium is also applied to reduce the cross-interference by guiding every femtocell user equipment's to achieve the target signal-to-interference noise ratio (SINR). From the numerical results, reduction in the high path loss on the desired signal in the heterogeneous downlink networks can be achieved by spatially reducing the larger antenna arrays and occurred when the mm-wave for distributed transmit power is larger than the threshold power.